Mutual influence of currents in plane inductor system with solenoid between two massive conductors - Batygin, Yu.V.; Shinderuk, S.O.; Chaplygin, E.O. (National Technical University "Kharkiv Polytechnic Institute" and Аnatolii Pidhornyi Institute of Power Machines and Systems of NAS of Ukraine, 2021)
Introduction. Inductor systems, as tools for metal processing, widely used in industrial  technologies  using the energy of powerful pulsed electromagnetic fields. Problem. A common disadvantage of the known works on the creation of tools for magnetic-pulse impact on conductive objects has the use of physical and mathematical models, in which the exciting currents do not depend on the ongoing electromagnetic processes. Such the assumption, have distorts the picture of the real energy in the working area of the inductor system. Goal. To obtain design ratios and numerical estimates of the mutual influence of exciting and induced currents of a flat inductor system with a circular solenoid located between massive well-conducting objects, moreover to carry out a theoretical analysis of electromagnetic processes in this system. Methodology. Have applied integrating Maxwell’s equations using the Laplace and Fourier-Bessel integral transformations in the approximation of the ideal conductivity of the metal objects to be processed. Results. The calculated relations for the theoretical analysis of electromagnetic processes have obtained in the high-frequency approximation. It shown that the inductance of the studied system decreases as the objects being processed approach the solenoid and increases as they move away from it. It found that for the invariability of the power indicators, of the proposed tool, a corresponding correction of the amplitude (on average up to 20 times) of the exciting current has necessary in the solenoid winding. Originality. For the first time, the tool design with a circular solenoid located between the massive metal objects has proposed for flat magnetic-pulse stamping. As a result of the theoretical analysis, the influence of electromagnetic processes on the currents flowing in the system has confirmed. Practical significance. The use of the results obtained will allow to increase the efficiency of the tool of magnetic-pulse technologies, and to reduce the energy costs for performing the specified production operations.